Chemistry today and tomorrow the central, useful, and creative science - Breslow, Ronald
"This highly readable book, written in nontechnical language, surveys the vast field of chemistry by looking at the practical contributions that chemistry makes to civilized life and by explaining how chemists make these contributions. Its eight chapters discuss broad disciplines of chemistry, such as medicinal, environmental, or industrial chemistry, but always with an eye for the interesting detail and for the human activity that lies behind these fields. Written in a lively question-and-answer format by award-winning teacher and researcher Ronald Breslow, recipient of the U.S. National Medal of Science in 1991, this book examines chemistry as it exists today but also identifies the primary challenges and problems that remain for the future. Young people thinking about scientific careers, parents and guidance counselors, or any readers curious about how chemistry affects the world they live in will benefit from this insightful book."--Book jacket.